Primary versus Secondary Immune Thrombocytopenia (ITP): A Meeting Report from the 2023 McMaster ITP Summit - Modi, Dimpy; Chowdhury, Saifur R.; Mahamad, Syed; Modi, Hayley; Cines, Douglas B.; Neunert, Cindy E.; Al-Samkari, Hanny; Cooper, Nichola; Moulis, Guillaume; Cunningham-Rundles, Charlotte; Liebman, Howard A.; Bussel, James B.; Breakey, Vicky R.; Nazy, Ishac; Arnold, Donald M. (Thrombosis and Haemostasis, 2025)
The McMaster Immune Thrombocytopenia (ITP) Summit, held on October 27, 2023, was an educational seminar from leading experts in immune thrombocytopenia and related disorders geared toward hematologists, internists, immunologists, and clinical and translational scientists. The focus of the Summit was to review the mechanisms, diagnosis, and treatment of primary versus secondary ITP. Specific objectives were to describe the unique features of secondary ITP, and to review its mechanisms in the context of autoimmune disease and infection. The key messages in this Summit were: (1) ITP is a heterogeneous disease, and genetic and immunologic insights may help classify patient subtypes; (2) exploring the autoimmune mechanisms and their association with hypogammaglobulinemia in patients with secondary ITP could improve our understanding of ITP and its subtypes; (3) investigating the mechanisms of ITP in the context of infections caused by viruses such as CMV, HIV, dengue, and hepatitis C, or bacteria such as H. pylori, or vaccinations could provide insight into the causes of ITP. A better understanding of secondary ITP could help elucidate the pathogenesis of ITP.
Keywords: bleeding; immune thrombocytopenia; platelet; immunology; infection